Weaknesses in Writing Narrative Texts among Fourth Grade Students at SD Negeri 79 Kota Bengkulu - Saputra, Yayan; Yumarni , Asmara; Meddyan Heriadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the weaknesses of fourth-grade students at SD Negeri 79 Bengkulu City in writing narrative compositions and to identify the contributing factors. The research employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal three main areas of weakness: content, language, and technical aspects. In terms of content, students’ narratives often lack coherent plots, underdeveloped ideas, and unclear beginnings, middles, and endings. From the language aspect, students show limited vocabulary, frequent errors in spelling, punctuation, and capitalization. Technically, weaknesses are found in paragraph organization and ineffective sentence structures. These difficulties stem from internal factors, such as low motivation, limited vocabulary, and poor idea organization, as well as external factors, including monotonous teaching methods, insufficient teacher guidance, lack of family support, and the influence of environment and social media. The study highlights the need for varied teaching strategies, stronger collaboration between teachers and parents, and consistent literacy practices to improve students’ narrative writing skills.